Cybercrime Correlates Among Adolescents in Europe and South America: A Cross-National Analysis Based on Situational Action Theory - Vepsäläinen, Janne (Journal of contemporary criminal justice, 2025)
Cybercrime is increasingly recognized as a global issue, with adolescents being a key group as crime trends shift online. However, relatively little is known about the prevalence of cybercrime, its specific risk factors, and how they differ across high and low-middle-income countries. This highlights the need for more cross-national comparative studies on the cybercriminal behavior of young people. This study examines the prevalence of four types of cybercrime (image-based abuse, online hate speech, cyberfraud, and hacking) among adolescents aged 13 to 17 in Europe and South America (N = 28,325). Utilizing data from the International Self-Report Delinquency Study 4 (ISRD4), the analysis includes nine countries from Europe (Denmark, Estonia, Finland, Iceland, Lithuania, Norway, Slovenia, Sweden, and the United Kingdom) and three from South America (Argentina, Brazil, and Venezuela). According to our results, there is variation in adolescent cybercrime offending between countries and continents. Overall, cybercrime and hacking were more common in South America, whereas image-based abuse was more prevalent among adolescents from Europe. Cybercrime was associated with low self-control, morality, and anticipated formal sanctions for cybercrimes, whereas peer delinquency was associated with a higher likelihood of offending. In line with situational action theory (SAT), peer delinquency and anticipated formal sanctions for cybercrimes were associated with cybercrime only among those with low or average morality.